Group cooperative midcourse guidance law based on multi-layer architecture for intercepting maneuvering target - Zhang, Ruitao; Guo, Hang; Chen, Zhan; Fang, Yangwang; Fu, Wenxing (Journal of the Franklin Institute, 2025)
To address the actual demand for multi-missile cooperative interception of multi-maneuvering targets, based on the differences in the multi-missile communication network structures, a decentralized group cooperative midcourse guidance law (GCMGL) and a distributed GCMGL are proposed. Firstly, a three-dimensional (3D) guidance model is established. Secondly, considering the adverse effects of target maneuvering on the guidance system, an adaptive fixed-time sliding mode disturbance observer (AFSMDO) is proposed to compensate the target acceleration, and the fixed-time stability of the system is proven using the Lyapunov stability theory. Then, when the multi-missile communication network structure is decentralized, based on the first layer of the trajectory shaping guidance law (TSGL) and the second layer of the cooperative midcourse guidance law with the virtual collision point as the cooperative term, a consensus protocol with the average total flight time of the group as the cooperative variable is designed in the third layer, so that the missiles of different groups can arrive at the mid-terminal handover area simultaneously. When the multi-missile communication network structure is distributed, based on the first layer as the TSGL, the second layer is designed with the time-to-go as the cooperative variable to ensure that the virtual collision point tends to the local average virtual collision point. The third layer is designed with the local average total flight time as the cooperative variable to ensure that the local average virtual collision points tend to be consistent, to ensure that the missiles from different groups reach the mid-terminal handover area simultaneously. Finally, the numerical simulations demonstrate the effectiveness and superiority of the proposed GCMGLs and AFSMDO.